Analysis of How Critical Thinking Skills Affect Students' Essay Writing Ability - Satuti, Retno; Winarni, Retno; Santosa, Eka Budhi (Universitas Sebelas Maret, 2025)
This study aims to analyze the influence of critical thinking skills on the essay writing ability of elementary school students. The research was conducted at SDN Gugus Gajah Mada Giriwoyo using a quantitative ex post facto approach. The research sample consisted of 52 students determined through cluster random sampling techniques. Critical thinking skills data were obtained based on scores on several essay questions, while essay writing skills were measured based on indicators of coherence, cohesion, sentence structure, and idea development. Data analysis employed descriptive statistics, normality tests, validity tests, and simple regression analyses. The results showed that critical thinking skills had a significant impact on the ability to write essays, accounting for 37% of the variance. These findings confirm the importance of integrating critical thinking-based learning in literacy learning in elementary schools.